Aulo Gelli, Pre-School Meals as a Platform for Behavior Change at Community Level: A Cluster Randomized Trial - Gelli, Aulo (2019)
Aulo Gelli POLICY SEMINAR Using Malawi’s Community-Based Childcare Centers to Implement an Agriculture and Nutrition Intervention Co-organized by IFPRI, the University of Washington led SEEMS nutrition project, and the CGIAR Research Program on Agriculture for Improved Nutrition and Health (A4NH)